2017
DOI: 10.1371/journal.pone.0187686
|View full text |Cite
|
Sign up to set email alerts
|

Impact of grazing dairy steers on winter rye (Secale cereale) versus winter wheat (Triticum aestivum) and effects on meat quality, fatty acid and amino acid profiles, and consumer acceptability of organic beef

Abstract: Meat from Holstein and crossbred organic dairy steers finished on winter rye and winter wheat pastures was evaluated and compared for meat quality, fatty acid and amino acid profiles, and consumer acceptability. Two adjacent 4-ha plots were established with winter rye or winter wheat cover crops in September 2015 at the University of Minnesota West Central Research and Outreach Center (Morris, MN). During spring of 2015, 30 steers were assigned to one of three replicate breed groups at birth. Breed groups were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Based on results from this study and the previous supplemental study by Phillips et al [18], winter rye and winter wheat forages are viable options for cattle grazing in the early spring and summer in the Midwest of the USA. Results suggested that winter rye might offer more herbage mass in the early spring at the expense of lower crude protein and 18:3 n -3 concentration compared to winter wheat.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Based on results from this study and the previous supplemental study by Phillips et al [18], winter rye and winter wheat forages are viable options for cattle grazing in the early spring and summer in the Midwest of the USA. Results suggested that winter rye might offer more herbage mass in the early spring at the expense of lower crude protein and 18:3 n -3 concentration compared to winter wheat.…”
Section: Discussionmentioning
confidence: 58%
“…Beef lipid FAs of this study are presented in Phillips et al [18]. Briefly, beef lipids from steers grazed on WR and WW differed ( P < 0.05) in butyric acid (4:0), tetradecenoic acid (14:1 trans ), myristoleic acid (14:1), hexadecenoic acid (16:1 trans ), margaroleic acid (17:1), octadecadienoic acid (18:2 trans ), gamma-linolenic acid (18:3 n -6), eicosatrienoic acid (20:3 n -3), arachidonic acid (20:4 n -6), heneicosanoic acid (21:0), and docosadienoic acid (22:2 n -6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Model integrated systems were established as observational study sites at the University of Minnesota West Central Research and Outreach Center (Morris, MN), the Rodale Institute (Kutztown, PA) and an on-farm site in Iowa (Erlandson Farm, Greenfield, IA). Specific details of the model system design and grazing regime are described in Phillips et al (2017). Briefly, 3-year integrated system rotations were established within 10-to 50-ha sites in Fall 2015-Spring 2016 that included small grain forages of rye (Secale cereale L.) and wheat (Triticum aestivum L.) for grazing the first year, followed by row crops of soybeans (Glycine max L.) and corn (Zea mays L.), and then a mixed-species pasture of fescue (Festuca arundinacea L.), orchardgrass (Dactylis glomerata L.), red clover (Trifolium pratense L.) and white clover (Trifolium repens L.) (Fig.…”
Section: Experimental Design and Sampling Overviewmentioning
confidence: 99%
“…Currently, rye is cultivated mainly in Europe as a grain crop [1], a number of countries use it as green fodder for domestic [4,5] and wild animals [6]. Due to its content with a number of valuable amino acids, the rye grain is a good additive to feed dairy and beef cattle, and with the use of certain feeding technologiesfor poultry and its young growth [7,8].…”
Section: Introductionmentioning
confidence: 99%